Towards a Liberal-socialist Reconstruction of the Social Contract: some Reflections from Norberto Bobbio’s Approach - Valenzuela, María (2021)
The notion of democracy is traditionally associated with the emergence and consecration of principles such as freedom and equality, on the basis of which the State established by the social contract is founded. The following article aims to explore the notion of social contract and the possibility of a re-elaboration of it based on the reconciliation of the ideology of equality and freedom as values that underlie its formulation. For this, a review of the theories of classical contractualism will be carried out until tracing its imprintstraces in the so-called contemporary contractualism. Some critical positions regarding the social contract and its origins based on the mercantilist tradition and the liberal theory of the seventeenth century will be analyzed bellow finally, attempt to develop the viability of a liberal socialist thought towards a new foundation of the social contract, based on the postulates of the Italian philosopher and jurist Norberto Bobbio.